Artificial intelligence applications for health care - Ahirwal, Mitul Kumar; Londhe, Narendra D.; Kumar, Anil, 1980- ([Place of publication not identified] : CRC Press, 2022)
"This book takes an interdisciplinary approach covering health care, cognitive computing, and artificial intelligence. Data sets related to biomedical signals and images are explored, analysed, and processed including applications of computational intelligence techniques in medial datasets"--
1. A Survey of Machine Learning in Healthcare. 2. A Review on Biomedical Signals with Fundamentals of Digital Signal Processing. 3. Images in Radiology : Concepts of Image Acquisition and the Nature of Images. 4. Fundamentals of Artificial Intelligence and Computational Intelligence Techniques with their Applications in Healthcare Systems. 5.Machine Learning Approach with Data Normalization Technique for Early Stage Detection of Hypothyroidism. 6. GPU-based Medical Image Segmentation: Brain MRI Analysis Using 3D Slicer. 7. Preliminary Study of Retinal Lesions Classification on Retinal Fundus Images for The Diagnosis of Retinal Diseases. 8. Automatic Screening of COVID-19 based on CT Scan Images through Extreme Gradient Boosting. 9. Investigations on Convolutional Neural Network in Classification of the Chest X-Ray Images for COVID-19 and Pneumonia. 10. Improving the Detection of Abdominal and Mediastinal Lymph Nodes in CT Images Using Attention U-Net Based Deep Learning Model. 11. Swarm Optimized Hybrid Layer Decomposition and Reconstruction Model for Multi-Modal Neurological Image Fusion. 12. Hybrid Seeker Optimization Algorithm-Based Accurate Image Clustering for Automatic Psoriasis Lesion Detection. 13. A COVID-19 Tracker for Medical Front-Liners. 14. Implementation of One Dimensional Convolutional Neural Network for ECG Classification on Python. 15. Pneumonia Detectionfrom X-ray Images by Two Dimensional Convolutional Neural Network on Python Platform.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Industries / Service Industries; COMPUTERS / Machine Theory; MEDICAL / Administration; Artificial intelligence -- Medical applications; Medical informatics